Lip length and its correlation among different age group and gender in Nepalese Population - Sapkota, Binam; Rimal, Ujjwal (Orthodontic Journal of Nepal, 2021)
Introduction: The Dentofacial composition includes the lips and the smile as they relate to the face which provide the valuable information to the clinician when evaluating smile esthetics. Aims and objectives: To determine the relation of lip length and incisor visibility during rest and smile among different age groups and gender. Materials and Method: A cross sectional study was done in 158 participants of age group between 19-40 years and above. They were seated in an upright position at rest. Then the lip length was recorded with a calibrated digital caliper measuring from subnasale to stomion superius and categorized into short, normal and long lips. Similarly maxillary incisor visibility was observed on rest and during full smile. The data obtained were then analyzed with SPSS software (version 22) and student- t test and ANOVA test was used to compare the measurements. Results: It has been found that there is no significant of lip length in relation to gender and different age groups. Whereas average lip length has been found to be 21.2±2.3mm in male and 19.4±1.9mm in female. On the other hand significant difference is found in incisor visibility in different age groups and gender during smile. Conclusion: Within the limitation of the study, a significant difference has been found in the incisor visibility when compared between gender and age groups in full smile whereas there is no difference in the lip length in male and female group.